PENDEKATAN PEMBELAJARAN KOOPERATIF TIP ROLE PLAYING SEBAGAI UPAYA PENINGKATAN PENGETAHUAN TENTANG KESELAMATAN LALU LINTAS PADA ANAK USIA DINI - Nopani, Dalilah; Lestari, Devi Dwi; Sumiaji, Asep (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
The research objective is to find a way of improving young learners’ knowledge of trafficsafety by using the role playing type of cooperative learning.The research method was classroom action research conducted in two cycles each ofwhich consisted of four stages, namely planning, acting, observing, and reflecting. The researchsubjects were the students of Harapan Kindergarten, Gandok, Condongcatur, Sleman,Yogyakarta.The research results showed that the young learners’s knowledge of traffic safetyawareness improved as a result of the implementation of role playing type of cooperativelearning. In the role plays they played the roles of subjects and objects of the traffic activities.They understood what was wrong and what was right to do as users of streets.Keywords: Traffic Safety, Role Play, Young Learners